2014
DOI: 10.1159/000363696
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Development and Neuronal Myelination Are Altered with Growth Restriction in Fetal Guinea Pigs

Abstract: This study examines aberrant synaptogenesis and myelination of neuronal connections as possible links to neurological sequelae in growth-restricted fetuses. Pregnant guinea pig sows were subjected to uterine blood flow restriction or sham surgeries at midgestation. The animals underwent necropsy at term with fetuses grouped according to body weight and brain-to-liver weight ratios as follows: appropriate for gestational age (n = 12); asymmetrically fetal growth restricted (aFGR; n = 8); symmetrically fetal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 54 publications
6
40
0
Order By: Relevance
“…Both DSs and PNNs have been involved in the regulation of synaptic connectivity and plasticity [43][44][45][46]. Our results showing decreased DS levels in IUGR rabbits are in line with previously described studies on guinea pig and sheep model showing changes in DS density and morphology along with changes in synaptic receptors after acute and chronic intrauterine insults [16,[47][48][49]. On the contrary, although there is growing interest in the description of PNN alterations related to specific brain diseases such as Alzheimer disease, schizophrenia, and epilepsy [45,50], the pattern of alterations in the PNNs related to IUGR had not been previously evaluated.…”
Section: Discussionsupporting
confidence: 92%
“…Both DSs and PNNs have been involved in the regulation of synaptic connectivity and plasticity [43][44][45][46]. Our results showing decreased DS levels in IUGR rabbits are in line with previously described studies on guinea pig and sheep model showing changes in DS density and morphology along with changes in synaptic receptors after acute and chronic intrauterine insults [16,[47][48][49]. On the contrary, although there is growing interest in the description of PNN alterations related to specific brain diseases such as Alzheimer disease, schizophrenia, and epilepsy [45,50], the pattern of alterations in the PNNs related to IUGR had not been previously evaluated.…”
Section: Discussionsupporting
confidence: 92%
“…Although, there may be several neurodevelopmental changes, as observed by Piorkowska et al [2] , leading to cognitive deficits in the developing brain, it can be concluded from this study that a perturbed lipid composition induced by PU affects the membrane structure and fluidity, and may contribute to the cognitive deficits that were earlier reported [6,7] . However, Se or Zn supplementation reversed the alterations in lipid composition and membrane fluidity, and may thus be beneficial in restoring the lipid dyshomeostasis associated with PU.…”
Section: Resultssupporting
confidence: 51%
“…However, Se or Zn supplementation reversed the alterations in lipid composition and membrane fluidity, and may thus be beneficial in restoring the lipid dyshomeostasis associated with PU. The changes observed by Piorkowska et al [2] may also occur in our model, which should be further investigated in future studies.…”
Section: Resultsmentioning
confidence: 53%
“…Volume ↓ cerebrum, E60 [162] ↓cerebellum E60 [142,162] Myelination ↓cerebrum, cerebellum, CA1 hippocampus, dorsal fornix, dorsal fimbria, corpus callosum, periventricular white matter, parasagittal white matter [119,121,143,206] =/↓ spine, age dependent [119] = subcortical white matter, d65 [143] Delayed maturation of myelin [162] ↓cerebral cortex, striatum [108] Thinner sheaths, signs of degeneration [108] Damage + lesions in cerebrum [108] + lesions, gliosis, axonal degeneration [109] Oligodendrocytes ↑ numbers in cerebellum [162] ASTROGLIOSIS Cerebrum = E52 [119] ↑E60, E62 [119,162] = E65 [143] ↑cortex [108,109] Striatum ↑ [108] Cerebellum = [119] ↑ E60 [162] Hippocampus = E65 [143] [79] ↓11% [90] ↓17.3% [128,129] ↓10-18% [116,212] = [125] Forebrain ↓10-15% [79,85][129] ↓13-16% [145,162] ↓19% [212] = [125] Cortex ↓31% [128] ↓20% [217] Striatum ↓12% [212] Hippocampus = …”
Section: White Mattermentioning
confidence: 99%